Prevalence of Dental Caries in relation to Body Mass Index, Daily Sugar Intake, and Oral Hygiene Status in 12-Year-Old School Children in Mathura City: A Pilot Study - Prahlad Gupta; Nidhi Gupta; Harkanwal Preet Singh (Hindawi Limited, 2014)
Aim. To correlate the prevalence of dental caries to body mass index, daily sugar intake, and oral hygiene status of 12-year-old school children of Mathura city. Material and Methods. The study design was cross-sectional and included 100 school children aged 12 years (n=50 boys and n=50 girls) who were randomly selected from two schools based upon inclusion and exclusion criteria. Body weight/height was recorded and BMI was calculated and plotted on CDC-BMI for age growth charts/curves for boys and girls to obtain percentile ranking. Dental caries was recorded using WHO criteria. Oral hygiene status of the study subjects was assessed using oral hygiene index-simplified. Data regarding the daily sugar intake was recorded using 24-hour recall diet frequency chart. The data obtained was analysed using SPSS version 11.5 for windows. Result. Only 27 subjects were affected by caries. The mean DMFT/dmft was 0.37 ± 0.79 and 0.12 ± 0.60, respectively. Statistical analysis by means of a logistic regression model revealed that only oral hygiene status had a significant effect on caries prevalence (OR = 5.061, P=0.004), whereas daily sugar intake and body mass index had no significant effect. Conclusion. From the analysis, it was concluded that oral hygiene status had a significant effect on caries prevalence of 12-year-old school children of Mathura city.